2016
DOI: 10.1186/s13054-016-1242-4
|View full text |Cite
|
Sign up to set email alerts
|

Liver function predicts survival in patients undergoing extracorporeal membrane oxygenation following cardiovascular surgery

Abstract: BackgroundExtracorporeal membrane oxygenation (ECMO) represents a valuable and rapidly evolving therapeutic option in patients with severe heart or lung failure following cardiovascular surgery. However, despite significant advances in ECMO techniques and management, prognosis remains poor and accurate risk stratification challenging. We therefore evaluated the predictive value of liver function variables on all-cause mortality in patients undergoing venoarterial ECMO support after cardiovascular surgery.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
49
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 42 publications
6
49
1
2
Order By: Relevance
“…In this study hyperbilirubinemia is related to the liver dysfunction. Liver dysfunction is very common in patients with ECMO support due to the compromised hemodynamic condition caused by ECMO . When liver is injured by ischemia, the bilirubin uptake and bile secretion will be impaired resulting in hyperbilirubinemia .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study hyperbilirubinemia is related to the liver dysfunction. Liver dysfunction is very common in patients with ECMO support due to the compromised hemodynamic condition caused by ECMO . When liver is injured by ischemia, the bilirubin uptake and bile secretion will be impaired resulting in hyperbilirubinemia .…”
Section: Discussionmentioning
confidence: 99%
“…Bilirubin as the end product of heme catabolism is metabolized and excreted by liver. Hemolysis and liver hypoperfusion caused by ECMO techniques, abnormal liver function induced by cardiac failure and cardiac surgery before ECMO support may result in hyperbilirubinemia during ECMO support. Bilirubin at a high level can induce apoptosis, inflammation, and oxidative stress, which may lead to neural impairment , thrombocytopenia , and respiratory failure .…”
mentioning
confidence: 99%
“…Besides the understanding of underlying mechanisms of CNS events during ECLS, monitoring and timely recognition of the adequacy of brain perfusion or the onset of maladaptive changes and cerebral injury, either perfusion or structurerelated, is paramount, but mostly lacking in ECLS patients. On-line information about appropriateness of anticoagulation state and presence and extent of coagulation disorder, brain perfusion and onset of cerebral tissue injury, as well as information about vascular structural and functional integrity, are all part of the complex puzzle which constitutes the ECLS/ patient interplay which is, at the moment, poorly defined and understood (12)(13)(14)(15)(16)(17)(18). As mentioned, it is likely that CNS event-related etiology is multifactorial, but we are still far from understanding why some patients develop such brain damages and some not.…”
mentioning
confidence: 99%
“…More emphasis is currently applied in the search for enhanced brain monitoring (14)(15)(16)(17)(18), and this includes also the elucidation of not only overt brain injury, but also the impact of ECLS on more subtle and important aspects accounting for the neurocognitive status, particularly in children (19)(20)(21).…”
mentioning
confidence: 99%
“…Traditionally, the hepatic failure during ECLS was considered more a witness than an active element in determining a worse prognosis (16). Recently, Roth et al demonstrated that, in patients undergoing VA-ECMO following cardiovascular surgery, liver function tests (pre-ECMO alkaline phosphatase and total bilirubin) were strong predictors of short-and longterm mortality (17).…”
mentioning
confidence: 99%